Gender jako analytická kategorie pro porozumění sexuálnímu obtěžování - Kateřina Kolářová; Irena Smetáčková; Petr Pavlík (Gender a Výzkum, 2011)
In the article, the authors respond to the main arguments that were voiced during discussions of the results of the project ‘Sexual Harassment in Universities: Incidence and Perception’, which the authors’ team carried out in 2008–2009. They do not aim to defend the research itself, but rather to analyse the dominant discourse on sexual harassment in the Czech environment from a gender perspective. This is because they see a refusal to accept gender as a relevant analytical category. They argue for the fundamental role of gender in the conceptualization of sexual harassment and for further refinement of its significance in gender‑informed definitions of sexual harassment. In the authors’ opinion, these definitions do not sufficiently reflect the current state of gender theories. The main argument of the text concerns the relationship between sexual and gender‑motivated harassment. The gender perspective offers an intrinsically coherent conceptualization of sexual harassment, including its causes and options for handling individual cases. In the article, the authors discuss the extent to which the gender order is a precondition for sexual harassment. This view allows them to think also about the less discussed types of sexual harassment (e.g. homophobic harassment) or to consider the ambivalence of some situations in which sexual harassment occurs (i.e. the dynamics of pleasant and unpleasant feelings, women’s initiative, etc.). At the same time, it reveals that power inequalities do not result only from institutional hierarchies between teachers and students, but also from the logic of the existing gender order.